(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2005)
It has been established that in the temperature range 298–308 K in presence of cationic and anionic surfactants the rate of the reaction (Rr) H2O2+HOO– depends on the [S]0 by bell-shape curve. Wr has minimum value at [S]0 =ccm. At [S]0 >ccm in the system micelles are formed, which are more favorable medium for the reaction. Depending on the ratio of both S initial concentrations their mixtures show different calloid-chemical proporties. It is shown that Rr depends on them. The inverse w/oil micelles are more favorable medium for the studied reaction than the oil/w type direct micelles.